Religious Socialization and Self-Definition Among Black Undergraduate Women Attending Predominantly White Institutions. Issue 4 (August 2022) - Leath, Seanna; Hope, Meredith O.; Palmer, Gordon J. M.; Rose, Theda
To date, few scholars have explored religious and spiritual socialization among emerging adult Black women. In this study, we analyzed semi-structured interview data from 50 Black undergraduate women to explore associations between childhood religious socialization messages and current religious beliefs in emerging adulthood. Consensual qualitative methods revealed two broad domains and six themes. The first domain, "religious alignment, " included: (1) internalizing religion and (2) educating others on religious beliefs. The second domain, "religious departure, " included: (3) modifying religious expectations to fit developing beliefs, (4) employing religion as a pathway to self-acceptance, (5) picking and choosing battles within their religious community, and (6) choosing an alternate religious or faith system. Findings highlighted how the women started to take ownership of their religious experiences, as well as how they used religious practices, such as prayer, to cope with gendered racism. Authors discuss the implications of emerging adulthood on Black women's religious identities.